2014
DOI: 10.1007/s00438-014-0897-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of citrus ATP-citrate lyase genes and their transcript analysis in fruits reveals their possible role in citrate utilization

Abstract: ATP-citrate lyase (ACL, EC4.1.3.8) catalyzes citrate to oxaloacetate and acetyl-CoA in the cell cytosol, and has important roles in normal plant growth and in the biosynthesis of some secondary metabolites. We identified three ACL genes, CitACLα1, CitACLα2, and CitACLβ1, in the citrus genome database. Both CitACLα1 and CitACLα2 encode putative ACL α subunits with 82.5 % amino acid identity, whereas CitACLβ1 encodes a putative ACL β subunit. Gene structure analysis showed that CitACLα1 and CitACLα2 had 12 exons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 34 publications
0
39
1
Order By: Relevance
“…These results reveal the importance and irreplaceability of cytosolic acetyl-CoA. In a previous report, significantly increased citrate contents under mild drought stress or abscisic acid treatment in fruits can reduce ACL gene expression (Hu et al, 2015). Therefore, ACLs may also participate in other unknown regulatory networks.…”
Section: Edt1 Interaction With Aclb-1 To Form a Heteromultimeric Protmentioning
confidence: 50%
See 1 more Smart Citation
“…These results reveal the importance and irreplaceability of cytosolic acetyl-CoA. In a previous report, significantly increased citrate contents under mild drought stress or abscisic acid treatment in fruits can reduce ACL gene expression (Hu et al, 2015). Therefore, ACLs may also participate in other unknown regulatory networks.…”
Section: Edt1 Interaction With Aclb-1 To Form a Heteromultimeric Protmentioning
confidence: 50%
“…In plants, ACL is a cytoplasmic heterologous protein consisting of two subunits (ACLA and ACLB), probably in an A 4 B 4 configuration (Fatland et al, 2002). ACLA and ACLB are encoded by three and two genes, respectively, in Arabidopsis (Fatland et al, 2002;Hu et al, 2015). Previous study has shown that plants with reduced ACL activity achieved using antisense RNA technology have a complex, bonsai phenotype coupled with reduced accumulation of cuticular wax and excessive accumulation of starch and anthocyanin (Fatland et al, 2005).…”
mentioning
confidence: 99%
“…Beta-glucosidase catalyzes the hydrolysis of the glycosidic and release of glucose, which then entry into the glycolysis process. ATP-citrate lyase (ACL, EC4.1.3.8) is a key enzyme involved in TCA cycle, which catalyzes the cleavage of citrate to yield acetyl CoA, oxaloacetate, ADP, and orthophosphate, and the ACL gene was found to be induced under various stresses including low temperature and drought stimulus (Hu et al, 2015). Pyruvate dehydrogenase could exert a key role in linking the glycolysis to the TCA cycle by catalyzing the formation of an acetyl-CoA from pyruvate (Vuoristo et al, 2015), which is a vital rate-limiting step reaction that determines the rate and efficiency of TCA cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis , ACL is required for normal growth and development, and its overexpression activated the wax, cutin and rubber biosynthetic pathways (Fatland et al ., ; Xing et al ., ). In animals, ACL comprises one polypeptide, whereas in plants, it is composed of two distinct subunits, subunit A and subunit B (Hu et al ., ). However, neither phenotypes caused by mutations in ACL gene have been reported in plants nor the gene for ACL has been isolated in rice so far.…”
Section: Introductionmentioning
confidence: 97%